Improving Rehabilitation Information-Giving to Intensive Care Unit Survivors to Aid in Physical and Psychological Recovery - Fardanesh, Armin (Cureus, 2021)
Intensive care unit (ICU) survivors have an increased mortality rate and reduced quality of life associated with post-ICU syndrome: a triad of physical, psychiatric and cognitive decline. Following evidence on the benefits of early rehabilitation, the National Institute of Clinical Excellence (NICE) CG83 guidelines instruct the provision of rehabilitation information to ICU patients before discharge. Only 33% of UK trusts meet these guidelines. The aim of this project was to reach 100% patient and ICU therapist satisfaction with the rehabilitation information given before ICU discharge at Medway Maritime Hospital, within four months. Patient and therapist satisfaction was assessed using questionnaires at baseline and following each Plan-Do-Study-Act (PDSA) cycle. In PDSA1, a generalised rehabilitation information booklet was created and distributed to ICU survivors pre-discharge. For PDSA2, a personalised rehabilitation plan completed by therapists was added. During PDSA3, the booklet was enriched with mental health and speech and language therapy sections. Results showed a shift in patient satisfaction scores, indicating a significant change in the median from 20% at baseline to 87% after PDSA3. This was also reflected in the therapist satisfaction scores, which increased significantly from 60% at baseline to 100%. The introduction of a generalised information booklet, supplemented with a personalised recovery plan, is an effective way of increasing critical care patient and therapist satisfaction with post-discharge rehabilitation information provision. This should translate to greater patient engagement with rehabilitation and improved long-term outcomes. This is ever more pertinent, as the COVID-19 pandemic will exponentially increase the numbers of ICU survivors at risk of long-term morbidity and mortality.